Wanprestasi Dalam Perjanjian Pembiayaan Konsumen (Studi Putusan Nomor 11/Pdt.G/2022/PN Bkt) - Lestiani, Karina; Rahmayani, Nuzul; Andriaman, Mahlil (Universitas Batanghari Jambi, 2023)
Activities between consumers and consumer financing institutions will occur if there is an agreement. In an agreement, an action cannot be separated from a person who cannot fulfill his obligations so that it can be said to have committed a negligence or made a mistake which is called a default. This research discusses Defaults in Consumer Financing Agreements (Decision Study Number 11/Pdt.G/2022/PN BKt). This research raises two problems, namely 1) How is the implementation of the agreement in consumer financing default cases based on the decision of the Bukitinggi District Court Number 11/Pdt.G/2022/PN Bkt? 2) What is the analysis of the judge's considerations in settling default cases in consumer financing agreements based on Bukitinggi District Court decision No. 11/Pdt.G/2022/PN Bkt? This study uses a normative juridical method. The data source used is secondary data, namely data obtained through a literature study with primary legal materials, secondary legal materials and tertiary legal materials. Data collection was carried out by (normative juridical) by using library research (library research) which is a data collection tool that is not directed directly to research subjects. The data analysis used is a qualitative analysis. The results of the study show how the judge considers the settlement of default cases in consumer financing agreements based on the decision of the Bukitinggi District Court Number 11/Pdt.G/2022/PN Bkt and the legal consequences of engagement from a civil aspect in the occurrence of default for both parties in case Number 11/Pdt .G/2022/PN Bkt.. In this decision the judge decided that PT. Mandiri Tunas Finance who defaulted on CV. Roberto First Works. The judge should have decided based on the Civil Code, to determine whether someone has defaulted based on the provisions of Article 1238 of the Civil Code13. In this case the legal consequence of the engagement from a civil aspect in the occurrence of default for both parties is to punish PT. Mandiri Tunas Finance to pay the costs of the case until the trial has been decided in the amount of Rp. 616,000 (six hundred and sixteen thousand rupiah).